Stability of interlanthanide perovskites ABO3 (A≡La–Pr; B≡Y, Ho–Lu). (April 2016) - Artini, Cristina; Pani, Marcella; Lausi, Andrea; Costa, Giorgio A.
Abstract: The existence fields of the 11 known interlanthanide perovskites have been assessed as a function of temperature on the basis of experimental and literature data, and studied by means of the bond valence method using the software SPuDS. The role of geometrical factors in driving the enthalpic and entropic contributions to the Gibbs free energy of the phase is discussed, and a criterion is proposed to derive the formability likelihood of interlanthanide perovskites. The reliability of the software SPuDS has been checked by comparing the cell parameters and atomic distances optimized by the program to the ones experimentally obtained by high temperature in situ synchrotron X-ray diffraction performed on perovskitic LaErO3, LaTmO3 and LaYbO3 . Graphical abstract: Highlights: The stability of interlanthanide perovskites has been investigated. Perovskitic structures were optimized by the bond valence method using SPuDS. The reliability of SPuDS was checked by comparing experimental and calculated data. A stability criterion was deduced by studying the geometrical limits of the phase. The criterion was verified applying it to non-perovskitic interlanthanide oxides.